Hertfordshire sarcopenia study: design and methods - Patel, H; Syddall, H; Martin, H; Stewart, C; Cooper, C; Sayer, A (BioMed Central, 2010)
Background: Sarcopenia is defined as the loss of muscle mass and strength with age. Although a number of adult influences are recognised, there remains considerable unexplained variation in muscle mass and strength between older individuals. This has focused attention on influences operating earlier in life. Our objective for this study was to identify life course influences on muscle mass and strength in an established birth cohort and develop methodology for collection of muscle tissue suitable to investigate underlying cellular and molecular mechanisms. Methods: One hundred and five men from the Hertfordshire Cohort Study (HCS), born between 1931 and 1939 who have historical records of birth weight and weight at one year took part in the Hertfordshire Sarcopenia Study (HSS). Each participant consented for detailed characterisation of muscle mass, muscle function and aerobic capacity. In addition, a muscle biopsy of the vastus lateralis using a Weil-Blakesley conchotome was performed. Data on muscle mass, function and aerobic capacity was collected on all 105 participants. Muscle biopsy was successfully carried out in 102 participants with high rates of acceptability. No adverse incidents occurred during the study. Discussion: The novel approach of combining epidemiological and basic science characterisation of muscle in a well established birth cohort will allow the investigation of cellular and molecular mechanisms underlying life course influences on sarcopenia.